Safety and Immunogenicity of Adenovirus 35 Tuberculosis Vaccine Candidate in Adults with Active or Previous Tuberculosis A Randomized Trial - van Zyl-Smit, Richard N.; Esmail, Aliasgar; Bateman, Mary E.; Pau, Maria Grazia; Benko, Jacqueline; Kagina, Benjamin M. N. (American Journal of Respiratory and Critical Care Medicine, 2017)
Administration of tuberculosis (TB) vaccines in participants with previous or current pulmonary TB may have the potential for causing harmful postvaccination immunologic (Koch-type) reactions. To assess the safety and immunogenicity of three dose levels of the AERAS-402 live, replication-deficient adenovirus 35–vectored TB candidate vaccine, containing three mycobacterial antigens, in individuals with current or previous pulmonary TB. We performed a phase II randomized, placebo-controlled, double-blinded dose-escalation study in an HIV-negative adult South African cohort (n = 72) with active pulmonary TB (on treatment for 1–4 mo) or pulmonary TB treated at least 12 months before study entry and considered cured. Safety endpoints included clinical assessment, flow volume curves, diffusing capacity of the lung for carbon monoxide, pulse oximetry, chest radiograph, and high-resolution thoracic computerized tomography scans. Cytokine expression by CD4 and CD8 T cells, after stimulation with Ag85A, Ag85B, and TB10.4 peptide pools, was examined by intracellular cytokine staining.
Keywords: tuberculosis; TB vaccine; vaccine immunogenicity